Klasifikasi sentimen terhadap larangan pernikahan beda agama menggunakan metode Naive Bayes Classifier - Muhammad Rizki Syafapri; Elin Haerani; Iwan Iskandar; Liza Afriyanti (Computer Science and Information Technology, 2024)
Interfaith marriage is still a controversial issue in multicultural Indonesian society. The provisions of Law Number 1 of 1974 which prohibit interfaith marriages have triggered various responses in society. In 2023, the Supreme Court (MA) decided to prohibit religious courts from registering interfaith marriages. This further strengthened the controversy and sparked various reactions from the public. Platforms like Instagram have become a forum for people to express their various sentiments regarding this issue, ranging from support, rejection, to questions and doubts. This research classifies 1000 Instagram comments collected from five news social media accounts. These comments were labeled manually by an expert who works as an Indonesian language lecturer, so they were divided into 500 positive comments and 500 negative comments. After going through the text preprocessing process and TF-IDF weighting, the Naïve Bayes Classifier method succeeded in achieving the highest level of accuracy of 76% by using 10% of test data from the dataset to classify public sentiment towards the ban on interfaith marriage in Instagram comments.